13C-Urea Breath Test Accuracy for 'Helicobacter pylori' Infection in the Asian Population: A Meta-Analysis - Muhammad Aklil Abd Rahim; Fadzrul Hafiz Johani; Shamsul Azhar Shah; Mohd Rohaizat Hassan; Mohd Rizal Abdul Manaf (Ubiquity Press, 2019)
Background: 'Helicobacter pylori' ('H. pylori') infection is known to be associated with peptic ulcer and gastric cancer. Detection of 'H. pylori' infection is a significant part of peptic ulcer and gastric cancer prevention and management. 13C-urea breath test (UBT) provides a good option for the pathogen detection due to its accuracy and safety. Objective: This review aims to evaluate the 13C-UBT diagnostic accuracy studies conducted among Asian population and validate its use for the Asian population. Methods: Original articles were systematically searched in PubMed, Scopus, and Google Scholar using the PICOS strategy by applying relevant keywords. Only studies published in English and conducted in Asia were included. Our search returned 276 articles. After assessment, 11 articles which answered our research question and met the criteria set for systematic review and meta-analysis were accepted. A total of 15 study protocols were extracted from the 11 accepted articles. Findings: Majority of the studies were conducted in Hong Kong (six), followed by Taiwan (five), Japan (two), and one each in Singapore and Israel. All studies had used histology as part of its gold standard of reference. All but one study was performed on adult populations. The summary estimate for sensitivity was 97% (95% CI: 96, 98%), and specificity was 96% (95% CI: 95, 97%), with significant heterogeneity between studies. Adjusting for the dose (50 mg) and breath sample collection time (20 minutes) had improved both accuracy estimates and significantly reduced heterogeneity. Conclusion: This review supports the test-and-treat strategy for 'H. pylori' infection management. Prevalence and cost-effectiveness studies are mandatory for health authorities to adopt this strategy into national policy.